PREHISPANIC OCCUPATION IN SAN LORENZO ISLAND: INPUTS OF SAN LORENZO ARCHAEOLOGICAL PROJECT - Hudtwalcker Morán, José (2009)
The cultural evidences registered and investigated for the San Lorenzo Island Archaeological Project suggest that during island’s prehispanic occupation, the main settlement concentrated on the southern tip of the island, at Caleta de la Cruz. There, a temporary fisher’s camp – and/or guano collectors -- and a cemetery were found. Chronologically, this occupation dates from the end of the Late Intermediate Period through the whole Late Horizon (XV – XVI Centuries A.D.). The presence of spondylus’s fragment and other objects with representations of fishes suggests rites with the cult to the sea and the islands, as well as with the “marine fertility”. The hypothesis of rites to the sea and the islands is sustained with the written sources of the colony, mainly with texts of century XVI and XVII. It is possible that during the prehispanic time the San Lorenzo island had ritual and economic use, which were integrated and complementary functions to each other.